Safety and necessity of omitting mediastinal lymph node dissection in cN0/N1 non-small cell lung cancer after neoadjuvant immunotherapy - Zhou, Yuheng; Zhai, Wenyu; Sun, Weizhen; Han, Yongping; Lin, Zhichao; Liu, Dihan; Zheng, Yan; Luo, Xiaojuan; Zhao, Zerui; Feng, Shoucheng; Lin, Yaobin; Tang, Hailin; et al. (Frontiers in Immunology, 2025)
BackgroundLymph nodes are crucial for perioperative immunotherapy but have to be completely resected in surgery. Trials evaluating the safety and necessity of omitting systemic mediastinal lymph node (mLN) dissection in non-small cell lung cancer (NSCLC) are still absent.MethodscN0/N1 NSCLC patients who received neoadjuvant immunotherapy and radical surgery were retrospectively collected from three institutions. Restricted cubic spline regression and receiver operating characteristic curve were used to analyze the association between mLN dissection number and survival outcomes. Confounding factors between selective and systemic mLN dissection groups were adjusted by inverse probability of treatment weighting (IPTW). The characteristics of memory CD8+ T cells in immunotherapy-treated mLN were identified by single-cell RNA and T-cell receptor sequencing (scRNA/TCR-seq) data retrieved from GSE185206.ResultsFrom 2019 to 2021, 131 neoadjuvant-treated cN0/N1 NSCLC patients were collected. The mLN clearance rate was 98.5% in the whole cohort and 100% in patients with radiologically confirmed complete response. Resected lymph node counts were irrelevant with local recurrence, distant metastasis, or death. Compared with selective mLN dissection, systemic mLN dissection did not show any survival benefit but showed slightly higher postoperative recurrence risk in both unadjusted and IPTW-adjusted cohorts. scRNA/TCR-seq showed that stem-like exhausted CD8+ memory T cells were the progenitors of tumor-specific CD8+ T lymphocytes in primary tumors and were abundantly enriched in resected mLN.ConclusionsOmitting systemic mLN dissection was safe in cN0/N1 NSCLC patients who received neoadjuvant immunotherapy. Excessive mLN dissection may disrupt the repertoire of stem-like exhausted CD8+ memory T cells and consequently impair the efficacy of adjuvant immunotherapy.